Optimal Feeding Strategy on Microalgae Growth in Fed-Batch Bioreactor Model - Nailul Izzati; Mardlijah Mardlijah (LPPM Institut Teknologi Sepuluh Nopember, 2015)
Some countries in the world turn to alternative energy source to fulfill their necessity of fuel. One of the alternative fuels is biodiesel. Raw material of biodiesel can be produced by microalgae cultivation in fed-batch bioreactor. To improve the productivity of microalgae cultivation, we need to determine the optimal control of microalgae growth. This paper discusses mathematical model of microalgae growth in fed-batch bioreactor, and solves the optimal feeding strategy problem by using Pontryagin Minimum Principle. Then we compare the controlled microalgae growth model with the uncontrolled one. Numerical simulation with DOTcvpSB shows that the controlled microalgae growth model yields more harvest and less cost function than the uncontrolled one.